The impact of a People's Republic of China slowdown on commodity prices and detecting the asymmetric responses of economic activity in Asian countries to commodity price shocks - Atanu Ghoshray; Madhavi Pundit (Asian Development Bank (ADB), 2016)
The recent slowdown of the People's Republic of China (PRC) has led to question to what extent the PRC demand of commodities can have an impact on commodity prices. We take into account the fact that commodity prices are characterized by structural breaks, and to this end we make use of novel econometric procedures incorporating the Flexible Fourier Form when testing for causal relations between the PRC slowdown and commodity prices. We find varying degrees of response of the PRC slowdown on different commodity prices. Further, this study determines whether the economic growth in selected developing and emerging Asian countries that are heavily dependent on commodities respond in an asymmetric manner to positive commodity price shocks as opposed to negative price shocks. Adopting a structural dynamic regression and censoring positive and negative shocks, we find limited evidence of any asymmetric response of economic activity to positive and negative commodity price shocks.
Keywords: C22; C32; F43; O47; Q31; 330; commodity prices; economic growth; Flexible Fourier Form; impulse response analysis; PRC slowdown